Into the storm : violent tornadoes, killer hurricanes, and death-defying adventures in extreme weather - Timmer, Reed (Dutton, 2010)
Reed Timmer, a star of the Discovery Channel's Storm Chasers, takes readers inside the awe-inspiring world of big weather. Featuring stories of the over 300 tornadoes, hurricanes, or blizzards that Timmer has watched ringside over the last decade, from Hurricane Katrina to little-studied storm systems in places like Canada and Argentina. A Ph.D. candidate in meteorology, Timmer is after more than just an adrenaline rush, his stories feature insights into the science of storms, and how the data he is collecting could possibly save lives. He also takes readers inside the storm-chasing community, examining his controversial obsession and the ethical debates it sparks.--From publisher description.